Association between sleep habits and height in children from low socioeconomic backgrounds: A cross-sectional study - Hanindita, Meta Herdiana; Widjaja, Nur Aisiyah (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Good sleep habits, including sleep duration and sleep onset, are crucial for supporting optimal growth and development. Literature suggests that insufficient sleep duration is associated with the risk of overweight and obesity in children. However, the relationship between sleep duration and sleep onset and height in children with a low socioeconomic status has not been explored. This study aims to investigate the association between sleep duration, sleep onset, and the height of children with a low socioeconomic status. Methods: A cross-sectional study was performed from October to November 2022 across five primary schools in Surabaya, involving second and third graders. Participants’ weight and height were measured, and they answered structured questionnaires. If children were unsure of answers, the forms were taken home for parental assistance. Inclusion criteria were students from households earning below the regional minimum wage, excluding those with incomplete data or chronic illnesses. Results: Among the 264 participants (47.7% boys, 52.3% girls, average age 108.7 ± 7.9 months), significant associations were observed between sleep duration and height (r=0.205, P=0.004) as well as sleep onset and height (r=0.397, P<0.0001). No significant links were found between sleep and weight. However, sleep duration and onset were significantly associated with screen time (P=0.025 and P<0.0001, respectively). Conclusions: Insufficient sleep duration and late bedtimes are strongly linked to shorter height in children from low-income families. Beyond duration, sleep timing also emerges as a critical factor in supporting optimal growth.